ANALISIS STRATEGI SALURAN DISTRIBUSI MINYAK PELUMAS ENDURO PADA PT. ARJUNA LUMAS DWIGUNA PEKANBARU - Benny Siboro; Jushermi '; Henni Noviasari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The purpose of this study to determine the management of distribution channels that include market coverage, cost, and control in increasing the sales volume of lubricating oil Enduro at PT. Arjuna Lumas Dwiguna Pekanbaru. Data analysis method used is descriptive analysis.Based on the results of research and discussion, it can be concluded that the management of distribution channels used by PT. Arjuna Lumas Dwiguna Pekanbaru is not optimal. In terms of market coverage PT. Arjuna Lumas Dwiguna Pekanbaru has marketed its products in five districts/cities located in Riau Province. PT. Arjuna Lumas Dwiguna Pekanbaru managed to increase sales of lubricating oil by Enduro innovations, promotions, and even provide training for agents/sales force there. PT. Arjuna Lumas Dwiguna Pekanbaru always evaluating the Enduro lubricating oil revenues so that distribution channel strategy which is seen well maintained and even enhanced marketing strategies that is deemed unfavorable updated in order to increase sales. The availability of the fleet itself as a means of transportation can reduce operating costs there by increasing revenue for PT. Arjuna Lumas Dwiguna Pekanbaru.Keywords : Distribution Channels , Market Coverage , Cost , Control , Sales Volume